THE CORRELATION BETWEEN STUDENTSâ€™ MOTIVATION AND THEIR SPEAKING SKILL - Nira Herdiani; Anne Ratna Suminar (English Education and Applied Linguistics Journal (EEAL Journal), 2020)
This paper entitled â€œThe Correlation between Studentsâ€™ Motivation and Their Speaking Skillâ€. The writer conducted research at one of senior high school in Garut. This research is aimed to find out there is any significant difference between motivation and speaking skill. The research procedures of this research are: first, the writer made instrument, second the writer give questionnaire motivation trait, third the writer doing interview on answer was choose, last the writer conducted data and reported data. After the writer calculated the data used T-test, it showed mean (x) of students motivation is 2.375 and the mean (x) of students speaking skill is 2.453 and then tcritical value by used significant level 0.05 is 2.0484 and t observed is 19,891 or tobserved â‰¤ tcritical. Based on the test hypothesis, and the curve of hypothesis testing showed the t test was on area of Ha acceptance. It means that there was significant difference between motivation and speaking skill